METHODOLOGICAL MODEL OF AN INTEGRATED APPROACH TO FINANCIAL AUDITING OF THE NATIONAL SYSTEM - Ramón Sakuray, Julio César (2016)
The office of the General Controller of the Republic (CGR) as the governing body of the National Control System, whose work its control over state resources, has not undergone substantial or structural modifications to reorient its actions towards improving control through approaches and / or models audit to guide its findings to the management of public entities. This article has a descriptive and explanatory character, based on the professional experience gained in the field of financial auditing and investigations conducted in relation to the work of supervision and control developed by the governing body of the National Control System. To achieve our goal, we proceeded to conduct a survey to participants in our sample. The main data obtained is that the National Control System currently does not allow a comprehensive assessment of management and its financial impact and budgetary, reflected in the financial statements and budget statements. To validate the efficient, effective and economical use of state resources, it is priority that the Government Financial Auditing-with an Integral approach- is applied promptly.